Dampak Lingkungan dari Penambangan Pasir Ciapus dan Margin Usahanya - A Faroby Falatehan (Institut Pertanian Bogor, 2023)
Bogor is one of the cities with a very rapid development rate, so the need for sand for construction is very high. There are plenty of sand sources in Bogor, feeding by 2 major rivers and 7 tributaries, including the Ciapus River. This river is a job opportunity for sand miners. Based on the study results, the traditional sand mining model is applied. The income from the sand miners is IDR100,000/m3, while the income from the collectors who also distribute the sand to the users is IDR150,000/delivery. The positive impact of this activity is that it can reduce sedimentation in the Ciapus River, while the negative impact is that it caused a change in the shape and function of the river and the road damage around the mining due to the sand transportation, but not on the road within the housing area. In the long term, this activity needs more attention because until now, the Bogor Kota Government still needs to have a regulation regarding type C mining. Keywords: type C mining, mining law, sand mining, sand transportation, traditional mining